ANALYSIS OF THE RAT FETUSES DEFINITIVE KIDNEY PECULIARITIES WHICH WAS DEVELOPED UNDER INFLUENCE OF NIMESULIDE - Shepitko, V.I.; Kcharchenko, S.V. (World of Medicine and Biology, 2013)
The definitive kidney rats embryo and fetus from 12 to day 22 of embryogenesis, which flows under the influence of nimesulide were investigated. It was determined that nimesulide disrupts the normal metanephric organogenesis. Changes in the morphology of the organ are shown for the first time in the 18-day-old and are most pronounced in this period of prenatal development. The presence of nephrons without vascular glomeruli in the renal corpuscles, congestion of blood vessels and areas of hemorrhage caused by the influence of all three doses of nimesulide (therapeutic, subtoxic and toxic). Clearly expressed by the linear dose-response effect.
Keywords: rats embryogenesis; kidney; nimesulid; cyclooxygenase-2